THE IMPACT OF STUTTERING ON THE ABILITY TO ACQUIRE ACADEMIC KNOWLEDGE IN CHILDREN OF SCHOOL AGE - Nada Dobrota-Davidović; Jadranka Otašević; Ljiljana Radević (Human Research in Rehabilitation, 2018)
The aim of this research was to establish the level of abilities that is a prerequisite for acquiring academic knowledge of children who stutter. The sample consisted of 102 subjects, of whom 42 children were experimental, and 60 children constituted a control group. We used following instruments: Riley test - a test for stuttering estimation, for quantitative speech analysis and ACADIA - a capacity assessment test that is a prerequisite for the acquisition of academic knowledge. The obtained results showed that there are differences in perceptual, visuo-motor, non-verbal and speech-language abilities of children stuttering in relation to children who do not stutter. There is a significant connection between the stuttering and the success of the Serbian language and the stutter and education of the parents. These differences should be used as the starting point in a therapeutic program for working with children who stutter